2011
DOI: 10.1152/ajpendo.00620.2010
|View full text |Cite
|
Sign up to set email alerts
|

Glucagon-like peptide-2-stimulated protein synthesis through the PI 3-kinase-dependent Akt-mTOR signaling pathway

Abstract: X. Glucagon-like peptide-2-stimulated protein synthesis through the PI 3-kinase-dependent Akt-mTOR signaling pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 31 publications
3
20
0
Order By: Relevance
“…The identity of the majority of the cells that expressed VIP after responding to the GLP-2 stimulus as neurons is clear; this was confirmed using antibodies for the pan-neuronal markers HuC/D and ␤-tubulin at each step of the effects of GLP-2 on differentiation (9, 11). Similar demonstrations of GLP-2 activation and regulation of neuronal phenotype have been shown in vivo in the ENS and in cultures of embryonic hippocampal neurons (31,33). However, a similar GLP-2-linked Akt-activated pathway was demonstrated in cultured astrocytes from the CNS (37,38).…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…The identity of the majority of the cells that expressed VIP after responding to the GLP-2 stimulus as neurons is clear; this was confirmed using antibodies for the pan-neuronal markers HuC/D and ␤-tubulin at each step of the effects of GLP-2 on differentiation (9, 11). Similar demonstrations of GLP-2 activation and regulation of neuronal phenotype have been shown in vivo in the ENS and in cultures of embryonic hippocampal neurons (31,33). However, a similar GLP-2-linked Akt-activated pathway was demonstrated in cultured astrocytes from the CNS (37,38).…”
Section: Discussionsupporting
confidence: 72%
“…Cells were isolated from rat colon or mouse ileum; protocols were approved by the University of Calgary Animal Care Committee, following the Canadian Council on Animal Care guidelines. Using previously described methods, primary cultures of submucosal neurons were prepared (5,16,31). In brief, animals (rats and mice aged 2-3 mo) were anesthetized using halothane by inhalation (Halocarbon Products, River Edge, NJ) and then exsanguinated.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, we aimed at evaluating the potential benefit of GLP-2 on In non-ischemic models of different tissues, GLP-2 effects were mediated by the activation of the prosurvival kinases ERK1/2 [1] or by PI3K/Akt-mTOR signalling pathway [39]. Several studies have demonstrated that activation of G protein-coupled receptors may lead also to PI3K/Akt activation and cardioprotective effects [8,31].…”
Section: Discussionmentioning
confidence: 99%
“…However, GLP-2R has the ability to couple to different G protein subunits and to activate multiple signalling pathways [18]. Studies using cells that naturally express the receptor suggest that phosphatidylinositol 3-kinase-γ[PI3Kγ] and subsequent Akt phosphorylation are the intracellular pathways activated by GLP-2 [19,20]. The enteric nervous system seems to be a key component in the GLP-2 action, and this was initially evident for one of the GLP-2's main activities, namely its ability to enhance intestinal epithelial growth.…”
Section: Introductionmentioning
confidence: 99%